"Bomb Explosion On The Nis Express" – Lessons From A Major Incident, Kosovo 16 Feb 2001. Issue 1 (1st March 2005) - Vassallo, D J; Graham, P J K; Gupta, G; Alempijevic, Dj
Abstract : On Friday 16 February 2001, terrorists detonated a bomb under a civilian coach travelling from Nis in Serbia to Gracanica in Kosovo. 10 people were killed at the scene. 13 casualties were treated in the British KFOR hospital (Reynolds Hospital) in Pristina. Another 8 casualties were evacuated to the American KFOR hospital at Camp Bondsteel. The incident provided a unique opportunity for co-operation between British, American, Russian, German and French KFOR hospitals, as well as with Serbian clinicians and forensic pathologists. This article analyses the medical management of this major incident, identifies the lessons to be learned from it, and also provides enough detail for teaching scenarios.